Electronic Properties of Armchair Black Phosphorene Nanoribbons Edge-Modified by Transition Elements V, Cr, and Mn - Jiong-Hua Huang (Nanoscale Research Letters, 2019)
Abstract The structural, electrical, and magnetic properties of armchair black phosphorene nanoribbons (APNRs) edge-functionalized by transitional metal (TM) elements V, Cr, and Mn were studied by the density functional theory combined with the non-equilibrium Green’s function. Spin-polarized edge states introduce great varieties to the electronic structures of TM-APNRs. For APNRs with Mn-stitched edge, their band structures exhibit half-semiconductor electrical properties in the ferromagnetic state. A transverse electric field can then make the Mn-APNRs metallic by shifting the conduction bands of edge states via the Stark effect. The Mn/Cr-APNR heterojunction may be used to fabricate spin p-n diode where strong rectification acts only on one spin.